Adsorption and conformation of serum albumin protein on gold nanoparticles investigated using dimensional measurements and in situ spectroscopic methods - Tsai, De-Hao (Langmuir : the ACS journal of surfaces and colloids, 2011)
The adsorption and conformation of bovine serum albumin (BSA) on gold nanoparticles (AuNPs) were interrogated both qualitatively and quantitatively via complementary physicochemical characterization methods. Dynamic light scattering (DLS), asymmetric-flow field flow fractionation (AFFF), fluorescence spectrometry, and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy were combined to characterize BSA-AuNP conjugates under fluid conditions, while conjugates in the aerosol state were characterized by electrospray-differential mobility analysis (ES-DMA). The presence of unbound BSA molecules interferes with DLS analysis of the conjugates, particularly as the AuNP size decreases (i.e., below 30 nm in diameter). Under conditions where the γ value is high, where γ is defined as the ratio of scattering intensity by AuNPs to the scattering intensity by unbound BSA, DLS size results are consistent with results obtained after fractionation by AFFF. Additionally, the AuNP hydrodynamic size exhibits a greater proportional increase due to BSA conjugation at pH values below 2.5 compared with less acidic pH values (3.4-7.3), corresponding with the reversibly denatured (E or F form) conformation of BSA below pH 2.5. Over the pH range from 3.4 to 7.3, the hydrodynamic size of the conjugate is nearly constant, suggesting conformational stability over this range. Because of the difference in the measurement environment, a larger increase of AuNP size is observed following BSA conjugation when measured in the wet state (i.e., by DLS and AFFF) compared to the dry state (by ES-DMA). Molecular surface density for BSA is estimated based on ES-DMA and fluorescence measurements. Results from the two techniques are consistent and similar, but slightly higher for ES-DMA, with an average adsorbate density of 0.015 nm(-2). Moreover, from the change of particle size, we determine the extent of adsorption for BSA on AuNPs using DLS and ES-DMA at 21 °C, which show that increasing the concentration of BSA increases the measured change in AuNP size. Using ES-DMA, we observe that the BSA surface density reaches 90% of saturation at a solution phase concentration between 10 and 30 μmol/L, which is roughly consistent with fluorescence and ATR-FTIR results. The equilibrium binding constant for BSA on AuNPs is calculated by applying the Langmuir equation, with resulting values ranging from 0.51 × 10(6) to 1.65 × 10(6) L/mol, suggesting a strong affinity due to bonding between the single free exterior thiol on N-form BSA (associated with a cysteine residue) and the AuNP surface. Moreover, the adsorption interaction induces a conformational change in BSA secondary structure, resulting in less α-helix content and more open structures (β-sheet, random, or expanded)